PENGARUH PENDEKATAN MULTI REPRESENTASI TERHADAP HASIL BELAJAR FISIKA DITINJAU DARI MOTIVASI BELAJAR PESERTA DIDIK - Aris Doyan; Muhammad Taufik; Raudah Anjani (Postgraduate, University of Mataram, 2018)
The purpose of this study is determine the effect of multi representation learning approaches to physics learning, the effect of students learning motivation on physics learning, and the interaction between the multi representational learning approach and the students learning motivation toward the learning outcomes of physics. This type of research is quasi experiment with non-equivalent group design. Sampling using purposive sampling technique, so that obtained class XI MIA 1 as experiment class and class XI MIA 2 as control class. The research instrument is a multiple choice test for physics learning result of 25 questions that have been tested for validity, reliability, level of difficulty, and different power of problems. The learning data of the two classes is normally distributed. Based on the homogeneity data obtained both homogeneous. Instrument to measure motivation to learn in the form of motivation questionnaire that has been tested by the expert team of validity. Data were analyzed by two-way ANOVA test. Result of data analysis show Ftable at 5% significance level equal to 3,97. Test the effect of multi representation learning approaches to physics learning equal to Fcount (8,857) > Ftable (3,97). Test the effect of students learning motivation on physics learning equal to Fcount (9.00) > Ftable (3,97). Test the interaction between the multi representational learning approach and the students learning motivation toward the learning outcomes of physics equal to Fcount (2.00) < Ftable (3,97). Based on these facts it can be concluded that there is influence of multi representation learning approach to physics learning result, there is influence of learning motivation learners to physics learning result, and there is no interaction between multi-representation learning approach with learning motivation of learners toward physics learning result.Keywords: multi representation learning approach, physics learning result, learning motivation